Policies for displaced workers: An american perspective - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 2010)
American employment policy for displaced workers started in the Great Depression with programs for the employment service, unemployment insurance, work experience, and direct job creation. Assistance for workers displaced by foreign competition emerged in the 1960s along with formalized programs for occupational job skill training. The policy focus on displaced workers was sharpened in the 1980s through the Worker Adjustment and Retraining Notification Act and the Economic Dislocation and Worker Adjustment Assistance Act. Field experiments on services to dislocated workers led to Worker Profiling and Reemployment Services systems in all states, and federal rules adopted as part of the North American Free Trade Agreement Act permitted UI benefit receipt while starting self-employment. Evaluation evidence suggests there should be continuous connection of unemployment compensation recipients to reemployment services, skill training closely connected to employer requirements, earnings supplements to ease transitions to different jobs, efforts to maintain and strengthen employer-employee relationships, information channels to employees and communities about impending employment disruptions, and targeting of services to improve returns on public investments. While no silver bullet emerges to solve worker displacement, many different programs addressing a variety of needs can improve labor market outcomes after permanent job loss.
Keywords: J65; J68; 330; displaced workers; reemployment; unemployment insurance; employment service; public employment policy; job training; wage subsidies; direct job creation; self-employment